Serum concentrations of human angiopoietin-like protein 3 in patients with nonalcoholic fatty liver disease: association with insulin resistance - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2009)
Objective Insulin resistance is considered a key feature of nonalcoholic fatty liver disease (NAFLD). In this setting, experimental studies have suggested a potential role of angiopoietin-like (ANGPTL) proteins in the pathogenesis of hepatic steatosis and the metabolic syndrome. In this study, we sought to investigate the plasma levels of ANGPTL protein 3 (ANGPTL3) - a liver-derived protein that modulates plasma triglyceride clearance - in patients with definite nonalcoholic steatohepatitis (NASH, n = 40), borderline NASH (n = 8), simple fatty liver (n = 9), and healthy controls without evidence of liver disease (n = 14). Methods Levels of ANGPTL3 were measured by enzyme-linked immunosorbent assay and compared in the four study groups. Moreover, concentrations of ANGPTL3 were assessed in relation to the general characteristics of the study participants and the results of liver biopsy. Results Levels of ANGPTL3 were significantly higher in patients with definite NASH (389 +/- 110 ng/ml, P < 0.05) and borderline NASH (433 +/- 70 ng/ml, P < 0.05) compared with controls (291 +/- 78 ng/ml). No significant differences were found in patients with simple fatty liver (321 +/- 119 ng/ml) as compared with controls. In correlation analyses of the entire study cohort, ANGPTL3 was significantly and positively associated with homeostatic model assessment for insulin resistance (r = 0.28, P < 0.05) but not with histological staging and pathological characteristics of NAFLD. Conclusion Although subject to future confirmation, our data suggest that ANGPTL3 levels are elevated in the more severe forms of NAFLD and could be associated with insulin resistance in this setting. Eur J Gastroenterol Hepatol 21:1247-1251 (C) 2009 Wolters Kluwer Health | Lippincott Williams & Wilkins.
Keywords: angiopoietin-like protein 3; biomarkers; liver injury; nonalcoholic fatty liver disease; METABOLIC SYNDROME; ANGPTL3; EXPRESSION; SECRETION